Mathematical communication of preservice mathematics teachers in solving gender-biased higher-order thinking skills problems - Sulistyawati, Eka; Radite, Ramadian (Universitas Islam Negeri Raden Intan Lampung, 2024)
Mathematical communication is a crucial 21st-century skill related to achievement and other skills. This study aims to analyze the differences in mathematical communication abilities and describe the difficulties male preservice teachers (MPT) and female preservice teachers (FPT) face in solving gender-biased Higher-Order Thinking Skills (HOTS) problems. This research employs a sequential explanatory mixed-methods design. The respondents, selected through purposive sampling, consisted of 4 MPTs and 10 FPTs. Data on mathematical communication abilities were obtained through a gender-biased HOTS problem-solving test. The respondents' difficulties in solving the problems were gathered through interviews. The results indicate differences between MPT and FPT mathematical communication skills using symbols and mathematical notation in solving problems. Student's difficulties in solving gender-biased HOTS problems are unfamiliarity and disinterest in the context. This study implies that education should emphasize contextual understanding and utilize gender-neutral problems to enhance mathematical communication skills.